2006
DOI: 10.1038/nature04311
|View full text |Cite
|
Sign up to set email alerts
|

Hit-and-run planetary collisions

Abstract: Terrestrial planet formation is believed to have concluded in our Solar System with about 10 million to 100 million years of giant impacts, where hundreds of Moon- to Mars-sized planetary embryos acquired random velocities through gravitational encounters and resonances with one another and with Jupiter. This led to planet-crossing orbits and collisions that produced the four terrestrial planets, the Moon and asteroids. But here we show that colliding planets do not simply merge, as is commonly assumed. In man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
264
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(271 citation statements)
references
References 41 publications
4
264
0
3
Order By: Relevance
“…The assumption to date has been that the larger of the two colliding bodies generally grows, but under some conditions a significant amount of material may be ejected (Asphaug et al 2006). This has two potential consequences.…”
Section: Formation Of the Earthmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption to date has been that the larger of the two colliding bodies generally grows, but under some conditions a significant amount of material may be ejected (Asphaug et al 2006). This has two potential consequences.…”
Section: Formation Of the Earthmentioning
confidence: 99%
“…The lower limit is certainly too low to account for the Earth's inventory of water, and the upper value may be only marginally generous enough provided the Earth sits near the dry end of its possible range of water values, and loss by impacts is minimal. In view of the fact that the upper value pertains to accretion prior to core formation, when the Earth was perhaps significantly less massive than today, loss of material (including water) during collisions with other embryos may have been too extensive (Asphaug et al 2006) to admit the carbonaceous chondritic source.…”
Section: Early Earth J I Lunine 1723mentioning
confidence: 99%
“…The anomalous eucrites could have avoided being shocked and brecciated during the Late Heavy Bombardment because at that time they were residing in small asteroids (~10 km in diameter) that had been derived earlier from Vesta-sized bodies. If the iron and stony-iron meteorites come from bodies that formed inside 2 AU and were eviscerated by protoplanetary impacts before reaching the asteroid belt (Bottke et al, 2006;Asphaug et al, 2006), this would help to explain why some differentiated asteroids were catastrophically destroyed but others were not. Vesta and the parent bodies of the anomalous eucrites might have escaped catastrophic disruption because they formed in the asteroid belt or because they were scattered there without being eviscerated.…”
Section: Origin Of Unbrecciated Eucritesmentioning
confidence: 99%
“…Numerous models (e.g. Benz & Asphaug 1999;Agnor & Asphaug 2004;Asphaug et al 2006) have reported that collisions are commonly nonaccretionary and lead to erosion of the outer layers of a growing planet. The inference that one might make here is that this process should have taken place at a very early stage (within the first few million years after the beginning of the Solar System) and have led to the removal of an early formed crust on the planetesimals that ultimately formed the Earth, Mars and the Moon.…”
Section: (B ) the Nd-isotope Composition Of The Terrestrial Planetsmentioning
confidence: 99%